Efektivitas Sanksi Terhadap Pengemis Di Jalan Umum Berdasarkan Pasal 504 Kitab Undang-Undang Hukum Pidana di Wilayah Hukum Kota Jambi - Suzanalisa, Suzanalisa; Supeno, Supeno; Kusumo, Wartono Triyan (Legalitas: Jurnal Hukum, 2023)
The Jambi City Government has regulated the handling of beggars on public roads in Article 504 of the Criminal Code. Of the many beggars in Jambi City, not all of them have been rehabilitated through the Jambi City Social Service and not a single beggar has been sanctioned on Jambi City's public roads. The aim of this research is to understand and analyze the factors that cause the number of beggars on public roads to increase in Jambi City, the effectiveness of sanctions against beggars on public roads based on Article 504 of the Criminal Code in the jurisdiction of Jambi City and the obstacles and efforts in Minimize begging on public roads in the jurisdiction of Jambi City. The theories used in this writing are effectiveness theory, criminology theory and effort theory. This type of research is empirical legal research. The discussion explains that the factors causing the increase in the number of beggars on public roads in Jambi City are physical condition and age, family economic conditions, employment opportunities, perception of begging, high income, begging is an easy job, strategic location and capital. The effectiveness of sanctions against beggars on public roads based on Article 504 of the Criminal Code in the jurisdiction of Jambi City has not been effective either by the city of Jambi, in this case the Jambi City Social Service, the Jambi City Civil Service Police Unit and the police due to misunderstandings related to the content. Article 504 of the Criminal Code. The obstacles and efforts in minimizing begging on public roads in the Jambi City jurisdiction are the lack of infrastructure and lack of legal understanding among the people of Jambi City. The efforts made are that the Jambi City Social Service formed a team to arrest beggars in Jambi City, carry out raids and train- training carried out by the Jambi City Social Service and the private sector.